Lingkungan Kerja sebagai Moderasi Hubungan Kepuasan Kerja dan Komitmen Organisasi terhadap Kinerja Pegawai Dinas Sosial Kabupaten Sleman - Arina Fauziah; Kusuma Chandra Kirana; Epsilandri Septyarini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the effect of job satisfaction and commitment on employee performance as well as the influence of the work environment in memorizing the relationship between job satisfaction and commitment to the performance of the Dinas Sosial Kabupaten Sleman employee. The population and samples used in this study were all employees of the Dinas Sosial Kabupaten Sleman who opened 60 employees using the saturated sample method. The data collection method used in this study is by using a questionnaire distribution. Analysis of the data used in this study is Partial Least Square (PLS) with the help of the SmartPLS 3.3.7 application through three stages of testing, namely: evaluation of the measurement model (outer model), evaluation of the structural model (inner model) and hypothesis testing. The results showed that there was a positive and significant effect of job satisfaction and organizational commitment variables on the performance of the Dinas Sosial Kabupaten Sleman employees. The work environment cannot moderate the relationship between job satisfaction and employee performance and the work environment can moderate the relationship between organizational commitment to employee performance. Keywords: Job Satisfaction, Organizational Commitment, Work Environment, Employee Performance